1998
DOI: 10.1002/(sici)1521-3935(19980201)199:2<283::aid-macp283>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycles 2. Living macrocyclic polymerization of -caprolactone with 2,2-dibutyl-2-stanna-1,3-dioxepane as initiator

Abstract: SUMMARY E-Caprolactone was polymerized in bulk at 80°C with 2,2-dibutyl-2-stanna-l,3-dioxepane (DSDOP) as initiator. The reaction time was varied for monomer/initiator molar ratios of 20, 100 and 500. A rapid and complete conversion of the monomer and only slight transesterification or back-biting degradation were found after longer reaction times. However, significant acceleration of these side reactions was observed at 180°C. Regardless of the M7I ratios and of the reaction time the polydispersities were nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 105 publications
(166 citation statements)
references
References 0 publications
8
158
0
Order By: Relevance
“…The above comment illustrates one of the reasons why the determination of molar mass by SEC with a refractive index or light scattering detector for polyesters is controversial in chloroform. Several authors have recently highlighted that polystyrene-calibrated SEC measurements in chloroform overestimate the real M n -by at least 50% in the range above 10 4 g·mol -1 for poly("-caprolactone), polylactide and related copolyesters [18][19][20][21][22][23][24]. For these reasons, researchers have used complementary techniques such as MALDI-TOF mass spectrometry [19,25].…”
Section: Introductionsupporting
confidence: 88%
“…The above comment illustrates one of the reasons why the determination of molar mass by SEC with a refractive index or light scattering detector for polyesters is controversial in chloroform. Several authors have recently highlighted that polystyrene-calibrated SEC measurements in chloroform overestimate the real M n -by at least 50% in the range above 10 4 g·mol -1 for poly("-caprolactone), polylactide and related copolyesters [18][19][20][21][22][23][24]. For these reasons, researchers have used complementary techniques such as MALDI-TOF mass spectrometry [19,25].…”
Section: Introductionsupporting
confidence: 88%
“…For most REPs of these monomers, the small Bu 2 Sn containing cycles summarized in Scheme 49 served as initiators [208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] above all the seven-membered dibutyl-2-stanna-1,3-dioxepane (DSDOP). [212][213][214][215][216][217][218][219][220] The first three examples presented in Scheme 49 were known from the work of several inorganic chemists for a long time, [165][166][167][168] but those authors did not use these heterocycles as initiators. In addition to these small cycles, cyclic oligomers such as the cyclosiloxane in Scheme 49 and the cyclic and spirocyclic oligo-and polyethers presented in Schemes 39 and 50 were used as initiators.…”
Section: Reps Of Cyclic Esters By Means Of Cyclic Tin Initiatorsmentioning
confidence: 99%
“…Therefore, cyclic polymers made via REP should give nearly pure ring structures in high weight fractions. The pioneering work by Kricheldorf et al 105,129,130 in this area showed that many different cyclic lactone and lactide monomer could be polymerized using the Bu 2 Sn initiator (Scheme 5). The main drawback is that the SnAO bond within the polymer is highly susceptible to hydrolysis, degrading to its linear analogue even in air.…”
Section: Ring-expansion Polymerizationsmentioning
confidence: 99%